2017
DOI: 10.1159/000478274
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Systemic Inflammatory Response following Robot-Assisted Laparoscopic Cystectomy vs. Open Mini-Laparotomy Cystectomy: A Prospective Study

Abstract: Introduction: Surgeries, such as radical cystectomy (RC), induce a systemic inflammatory response (SIR). SIR plays an important role in controlling the human immune system. This study aims at comparing the SIR in robot-assisted laparoscopic cystectomy (RALC) to open mini-laparotomy cystectomy (OMC) with a urinary diversion (UD). Comparison was based on immunologic markers of SIR, thus quantifying the degree of tissue trauma. Materials and Methods: Forty-two male patients underwent RC with an ileal conduit. Eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Regarding RARC, only recently 2 randomized trials reported similar oncological survival outcomes when compared to ORC [7,8]. Regarding laparoscopic RC, sufficient data from randomized trials comparing laparoscopic RC and ORC is scarce, similar oncological survival may be anticipated as well [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding RARC, only recently 2 randomized trials reported similar oncological survival outcomes when compared to ORC [7,8]. Regarding laparoscopic RC, sufficient data from randomized trials comparing laparoscopic RC and ORC is scarce, similar oncological survival may be anticipated as well [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Further, whether RARC adds advantages regarding other factors, for example, perioperative systemic inflammatory response is currently under investigation [7]. As far as oncological endpoints are concerned, RARC is reported to provide non-inferior positive surgical margin rate and lymph node yield [4,3].…”
Section: Introductionmentioning
confidence: 99%
“…In benign and malignant abdominal surgery, the immunological stress response has been studied in other closely related surgical specialities such as gynaecology and urology. However, most studies investigate the surgical stress response in robot-assisted versus open surgery, which is not comparable with this study as there is significantly more trauma with open surgery compared to minimally invasive surgery [ 10 , 37 40 ]. It is a common conclusion in many studies that robot-assisted surgery initiates a lower stress response.…”
Section: Discussionmentioning
confidence: 87%
“…To date, no randomized controlled trials comparing the systemic or peritoneal inflammatory response in colon cancer surgery performed by robot-assisted or laparoscopic methods has been published. A decreased systemic inflammatory response is associated with a lower risk of surgical complications and improved long-term oncological outcomes [ 10 ]. This response is due to a cascade of neuroendocrine, metabolic and immunological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, alterations in serum 8 and peritoneal exudate cytokine levels 9 have been associated with ileus, suggesting a relationship for further investigation. In this regard, previous studies have shown a reduction in proinflammatory cytokines and an increase in anti‐inflammatory cytokines in robot‐assisted cystectomy and abdominal surgery, 10,11 associated with a decrease in tissue damage and associated cytokine storm 12,13 . Furthermore, low‐pressure robotic surgery has been shown to improve patient outcomes and is associated with a decrease in surgical injury 14 …”
Section: Introductionmentioning
confidence: 98%